Statistical analysis of histopathological endpoints. (21st March 2014) - Green, John W.; Springer, Timothy A.; Saulnier, Amy N.; Swintek, Joe
Abstract Histopathological assessments of fish from aquatic ecotoxicology studies are being performed with increasing frequency. Aquatic ecotoxicology studies performed for submission to regulatory agencies are usually conducted with multiple subjects (e.g., fish) in each of multiple vessels (replicates) within a water control and within each of several concentrations of a test substance. A number of histopathological endpoints are evaluated in each fish, and a severity score is generally recorded for each endpoint. The severity scores are often recorded using a nonquantitative scale of 0 to 4, with 0 indicating no effect, 1 indicating minimal effect, through 4 for severe effect. Statistical methods often used to analyze these scores suffer from several shortcomings: computing average scores as though scores were quantitative values, considering only the frequency of abnormality while ignoring severity, ignoring any concentration–response trend, and ignoring the possible correlation between responses of individuals within test vessels. A new test, the Rao‐Scott Cochran‐Armitage by Slices (RSCABS), is proposed that incorporates the replicate vessel experimental design and the biological expectation that the severity of the effect tends to increase with increasing doses or concentrations, while retaining the individual subject scores and taking into account the severity as well as frequency of scores. A power simulation and examples demonstrate the performance of the test. R‐based software has been developed to carry out this test and is available free of charge at www.epa.gov/med/Prods_Pubs/rscabs.htm. The SAS‐based RSCABS software is available from the first and third authors. Environ Toxicol Chem 2014;33:1108–1116. © 2014 SETAC